The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11829-011-9124-9
|View full text |Cite
|
Sign up to set email alerts
|

The response of resistant kiwifruit (Actinidia chinensis) to armoured scale insect (Diaspididae) feeding

Abstract: The responses of five experimental genotypes and one commercial variety of kiwifruit (Actinidia chinensis) to attack by two polyphagous, congeneric armoured scale insect pests (Hemiberlesia rapax and H. lataniae) are described. H. lataniae feeding elicits a response in the bark and fruit of all but one of the experimental genotypes, leading to the development of wound periderm over a 4-5 week period, and death of the insect. The response, which differs slightly between tissue types and genotypes, consists of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
3
16
0
4
Order By: Relevance
“…The low deposition of phenolic compounds observed in branch sections with brown scales and two species of scale per branch section is possibly due to the branch already showing secondary growth. Hill et al (2011) observed that mature branches of kiwi (Actinidia chinensis) infested with H. lataniae showed a slower and less pronounced response to the colonization by this scale compared to that observed in young branches.…”
Section: Histological Response To the Colonization By Armored Scales mentioning
confidence: 84%
See 4 more Smart Citations
“…The low deposition of phenolic compounds observed in branch sections with brown scales and two species of scale per branch section is possibly due to the branch already showing secondary growth. Hill et al (2011) observed that mature branches of kiwi (Actinidia chinensis) infested with H. lataniae showed a slower and less pronounced response to the colonization by this scale compared to that observed in young branches.…”
Section: Histological Response To the Colonization By Armored Scales mentioning
confidence: 84%
“…No structural changes were observed in tissues of avocado branches in response to the colonization by armored scales (Figures 2A and 2B). Hill et al (2011) found that only some kiwi genotypes (Actinidia chinensis) infested with H. lataniae induced the formation of a wound at the point of contact between the periderm of the branch and the scales; the collenchyma cells showed accumulation of phenolic material, hypertrophy and cellular collapse. Fruto.…”
Section: Histological Response To the Colonization By Armored Scales mentioning
confidence: 99%
See 3 more Smart Citations